Multi‐"Color" Delineation of Bone Microdamages Using Ligand‐Directed Sub‐5 nm Hafnia Nanodots and Photon Counting CT Imaging. (6th November 2019) - Ostadhossein, Fatemeh; Tripathi, Indu; Benig, Lily; LoBato, Denae; Moghiseh, Mahdieh; Lowe, Chiara; Raja, Aamir; Butler, Anthony; Panta, Raj; Anjomrouz, Marzieh; Chernoglazov, Alex; Pan, Dipanjan
Abstract: The early detection of bone microdamages is crucial to make informed decisions about the therapy and taking precautionary treatments to avoid catastrophic fractures. Conventional computed tomography (CT) imaging faces obstacles in detecting bone microdamages due to the strong self‐attenuation of photons from bone and poor spatial resolution. Recent advances in CT technology as well as novel imaging probes can address this problem effectively. Herein, the bone microdamage imaging is demonstrated using ligand‐directed nanoparticles in conjunction with photon counting spectral CT. For the first time, Gram‐scale synthesis of hafnia (HfO2 ) nanoparticles is reported with surface modification by a chelator moiety. The feasibility of delineating these nanoparticles from bone and soft tissue of muscle is demonstrated with photon counting spectral CT equipped with advanced detector technology. The ex vivo and in vivo studies point to the accumulation of hafnia nanoparticles at microdamage site featuring distinct spectral signal. Due to their small sub‐5 nm size, hafnia nanoparticles are excreted through reticuloendothelial system organs without noticeable aggregation while not triggering any adverse side effects based on histological and liver enzyme function assessments. These preclinical studies highlight the potential of HfO2 ‐based nanoparticle contrast agents for skeletal system diseases due to their well‐placed K‐edge binding energy. Abstract : Bone as a functional material experiences various stresses that can lead to microdamages. Targeted hafnia nanoparticles are designed and used in photon counting spectral computed tomography for the detection of the microdamages. This advanced technology determines the signal from hafnia nanoparticles bound to the hard tissue of bone both in the ex vivo and in vivo models.